Transdutores ultra-sônicos piezoelétricos com difração limitada : simulação e construção - Ruiz, Alina Beatriz Aulet (2006)
The importance of ultrasound limited-diffraction Bessel beams in medical images, tissue characterization, and estimation of Doppler speed (blood flow) as well as in many other areas of Physics has increased in the two last decades. In this work an alternative solution to produce a transducer of limiteddiffraction was implemented, with the polarization following the geometry of the Bessel's function. These transducers (also called Bessel Transducers) have been constructed using a ferroelectric ceramic PZT doped with Niobium, by means of a simple technique of polarization. The electrodes in the faces of ceramics were made with a silver painting in form of three concentric rings. Through experimental simulations and measurements, the vibration's modes as well as the acoustic field of radiation has been characterized. For the simulation, the method of finite elements was applied. For these transducers it was verified a decoupling between the modes of radial and thickness vibration. The fields radiated have shown that there are less effects of diffraction on Bessel transducers than on the conventional transducers. With this new implemented technology, not reported before in the literature, the limited-diffraction transducer does not require a sophisticated electronic set up to excite acoustic waves in the transducer, allowing to get a collimated radiation field desirable for medical applications with optimized lateral resolution.